Assessment of Heavy Risk Factor Association with Lung Cancer Risk Using Questionnaire-Based Screening: A Cross-Sectional Study at Medan Johor Public Health Center, Medan, Indonesia - Muhammad Azka Auliya; Noni Novisari Soeroso; Rina Amelia; Dina Arwina Dalimunthe; Darren Wan-Teck Lim (Faculty of Medicine Universitas Airlangga, 2026)
Introduction: Lung cancer remains a major public health concern in Indonesia, characterized by high morbidity and mortality rates. Effective prevention and management strategies necessitate the accurate identification of lung cancer risk factors. The questionnaire was developed and validated as a screening tool to evaluate risk factors and generate lung cancer risk scores. This study aimed to assess the questionnaire’s utility for identifying lung cancer risk factors and categorizing risk levels among individuals at the Medan Johor Public Health Center, Medan, Indonesia. Methods: This study enrolled 180 subjects who met the inclusion criteria. These subjects were part of the population, specifically non-lung-cancer patients at the Medan Johor Public Health Center in Medan, Indonesia. A cross-sectional analytic design was used to examine the correlation between risk factors and risk levels. Results: Among 180 lung cancer patients screened, the tool classified most individuals into moderate- to high-risk strata and showed significant between-group differences for most risk factors (p<0.05). In addition, the Kenali Paru (NARU) screening tool is accessible, reproducible, and cost-effective, using a 14-item multiple-choice format (2-3 options per item) with weighted scoring that converts responses into a total risk score. Conclusion: The questionnaire demonstrates its effectiveness as a screening tool for identifying lung cancer risk factors and stratifying risk levels. Nevertheless, refinement is necessary to address its limitations, including the addition of tailored questions for sub-populations with specific comorbidities or health conditions.